2015
DOI: 10.3382/ps/pev070
|View full text |Cite
|
Sign up to set email alerts
|

The response of meat ducks from 15 to 35 d of age to gossypol from cottonseed meal

Abstract: The objective of this study was to investigate the responses of meat ducks of 15 to 35 d of age to free gossypol (FG) from cottonseed meal (CSM) and to establish the maximum limits of dietary FG concentration based on growth performance, blood parameters, and tissue residues of gossypol. Nine hundred 15-d-old ducks were randomly allocated to 5 treatments with 10 cages/treatment and 18 ducks/cage on the basis of BW. Five isonitrogenous and isocaloric experimental diets were formulated on a digestible amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
(42 reference statements)
6
18
0
1
Order By: Relevance
“…Zeng et al (2015) assessed the effect of using cottonseed meal as a replacement of soybean meal in the diet of meat type ducks. These authors found that various proportions of cottonseed meal replacement in the diet did not have an effect on the values of the RBC, which is in accordance with the findings in our study, where meal from whole white lupin seeds was used to replace soybean meal.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al (2015) assessed the effect of using cottonseed meal as a replacement of soybean meal in the diet of meat type ducks. These authors found that various proportions of cottonseed meal replacement in the diet did not have an effect on the values of the RBC, which is in accordance with the findings in our study, where meal from whole white lupin seeds was used to replace soybean meal.…”
Section: Discussionmentioning
confidence: 99%
“…Gossypol occurs in both a free and bound form (Zeng et al ). Free gossypol is the active form that readily causes toxic effects in vertebrates.…”
mentioning
confidence: 99%
“…Free gossypol might accumulate in animal tissues over time and have a negative impact on growth performance. Free gossypol toxicity is associated with alterations in blood parameters [15,16]. Gossypol may combine with iron, inhibit the synthesis of respiratory enzymes, and generate excessive reactive oxygen species in the mitochondria [17].…”
Section: Discussionmentioning
confidence: 99%